Compactness Results on Integro-Differential Equations Involving Ψ-Hilfer Fractional Derivative - Karthikeyan, P.; Karthikeyan, K.; Baleanu, D. (Discontinuity, Nonlinearity, and Complexity, 2026)
We analyze the existence results of fractional integro-differential equations via Ψ-Hilfer fractional derivative with nonlocal multi-point condition by using Schauder fixed point theorem. To establish the sufficient conditions for compactness of operators and an example is also discussed.